Vlog Media Utilization To Improve English Speaking Skills - Heri Pranata; Baiq Nadia Tiara Rizki (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The shifting of English language learning from conventional way to technology-based learning is popular nowadays. he development of technology has given a wide chance for students to find out the best media in supporting them to learn English. One of the media that can be used is Vlog. The main focus of the study was to describe the roles of video blog in improving speaking skill by students’ perspective. This study aims at identifying the improvement of the students’ performance after learning English using Vlog. This type of research is qualitative research. The subjects in this study were English Department Institut study Islam Sunan Doe, totaling 20 students. Data collection was done through interviews, observation and documentation. The results depicted that there is significant improvement towards students’ performance after learning English by using Vlog. Vlog benefits students in improving their English speaking ability. Students’ perspective on the use of video blog to improve speaking skill is good through various strategies. Furthermore, students have good English skills by using video blog as the media to learn English.